Mirror's edge - Alexander, Meena; Basualdo, Carlos; DeBord, Matthew; Enwezor, Okwui; Fischer, Jean; Lundström, Jan-Erik; Nilsson, John Peter; Tayou, Pascale Marthine; Vancouver Art Gallery, Vancouver; Castello di Rivoli, Torino; Tramway, Glasgow (Umea : BildMuseet, 1999)
Ackermann, Franz ; Alÿs, Francis ; Coleman, Beth ; Goldkrand, Howard ; Demand, Thomas ; Edefalk, Cecilia ; Floyer, Ceal ; Gaba, Meschac ; Garaicoa, Carlos ; Hirschhorn, Thomas ; Hakansson, Henrik ; Jafa, Arthur ; Kawakubo, Rei ; Kingelez, Bodys Isek ; Lundberg, Bill ; McQueen, Steve ; N55 ; Oguibe, Olu ; Pettibon, Raymond ; Roberts, Liisa ; Schonfeldt, Joachim ; Shonibare, Yinka ; Spaans, Peter ; Struth, Thomas ; Sugimoto Hiroshi ; Tayou, Pascale Marthine ; Tottie, Sophie
Speciale kast : mini-CD + zelfde code
biografie, bibliografie
Mirror's edge, BildMuseet, Umea, November 21, 1999 - February 20, 2000 ; Vancouver Art Gallery, Vancouver, March 18, 2000 - July 9, 2000 ; Castello di Rivoli, Torino, October 5, 2000 - January 14, 2001 ; Tramway, Glasgow, March 2, 2001 - April 15, 2001
Engels & Zweeds
kunstcatalogus